Proximate Composition and Nutritional Indices of Fenugreek Under Salinity Stress: The Role of Biocyclic Vegan and Other Organic Fertilization Systems in Forage Quality - Antigolena Folina; Ioanna Kakabouki; Panteleimon Stavropoulos; Antonios Mavroeidis; Eleni Tsiplakou; Dimitrios Bilalis (Crops, 2025)
Fenugreek (Trigonella foenum-graecum L.) is an emerging forage crop known for its high nutritional value and adaptability to diverse environmental conditions, making it a promising alternative in sustainable livestock feeding systems in the Mediterranean region. A field experiment was established at the Agricultural University of Athens during the growing season 2020–2021 in a split-plot design with five fertilization treatments (Biocyclic-Vegan Humus Soil; BHS, Farmyard Manure; FMA, Organic Compost; OCP, Inorganic Fertilizer; IFZ, and No Treatment Control; CTRL, and two main salinity treatments (High Salinity Level; HSL, and Normal Salinity Level; NSL). The Forage Quality Index (FQI) was the highest under BHS at NSL (45) and lowest under CTRL at HSL (32), emphasizing the positive impact of organic fertilization. Crude ash (CA) was higher under NSL (9.7%), with OCP and IFZ performing best, while salinity reduced CA under CTRL. Crude fiber (CF) increased under salinity, particularly with OCP and IFZ, whereas BHS and FMA at NSL showed the lowest CF (15.8%), enhancing digestibility. Total fat (TF) was the highest under BHS and FMA at NSL (5.8%) and lowest under IFZ and CTRL at HSL (4.0%), underscoring the importance of balanced fertilization in maintaining fat content. These results highlight the potential of organic amendments to improve nutrient availability, digestibility, and overall feed value.